Microstructural and electrochemical properties of Ti-doped Al2O3 coated LiCoO2 films - Choi, Ji-Ae; Lee, Seong-Rae; Cho, Won-Il; Cho, Byung-Won (KOREAN INST METALS MATERIALS, 2011)
We studied the microstructural and electrochemical properties of Ti-doped Al2O3 (Ti-Al2O3) coated LiCoO2 thin films depending on the Ti composition. The 1.27 at.% Ti-Al2O3 coated films had an amorphous structure with better conductivity than that of pure Al2O3 films. The Ti-Al2O3 coating layer effectively suppressed the dissolution of Co and the formation of lower Li conductivity SEI films at the interface between the LiCoO2 film and electrolyte. The Ti-Al2O3 coating improved the cycling performance and capacity retention at high voltage (4.5 V) of the LiCoO2 films. The Ti-Al2O3 coated LiCoO2 films showed better electrochemical properties than did the pure Al2O3 coated LiCoO2 films. These results were closely related to the enhanced Li-conductivity and interfacial quality of the Ti-Al2O3 film.
Keywords: LITHIUM BATTERIES; 4.5 V; INTERCALATION; CATHODE; R(3)OVER-BAR-M; BEHAVIOR